2017
DOI: 10.1080/10401334.2017.1365717
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Interprofessional Education and Cultural Competency Training to Address Health Disparities

Abstract: The program had to be flexible enough to meet the educational requirements and class schedules of the different health professions' education programs. The target community spoke limited English, so providing interpretation services using bilingual Marshallese community health workers was integral to the program's success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 31 publications
0
68
0
1
Order By: Relevance
“…Residents in our study reported a preference for cultural competency training and experiential learning to help them identify and address health disparities. While evidence regarding the effectiveness of cultural competency training for improving patient outcomes is mixed [27], research suggests that when combined with experiential learning, cultural competency training can help increase clinicians' awareness of their own biases and the needs of underserved and minority patients [28,29]. Academic medical centers can incorporate disparities-focused experiential learning using methods such as community-based teaching [30], simulations and community tours [31].…”
Section: Discussionmentioning
confidence: 99%
“…Residents in our study reported a preference for cultural competency training and experiential learning to help them identify and address health disparities. While evidence regarding the effectiveness of cultural competency training for improving patient outcomes is mixed [27], research suggests that when combined with experiential learning, cultural competency training can help increase clinicians' awareness of their own biases and the needs of underserved and minority patients [28,29]. Academic medical centers can incorporate disparities-focused experiential learning using methods such as community-based teaching [30], simulations and community tours [31].…”
Section: Discussionmentioning
confidence: 99%
“…Cultural safety includes, "the delivery of quality care through changes in thinking about power relationships and patients' rights" [252]. To this end, several programs exist that educate medical students about Indigenous health using collaborative and decolonizing methods [253][254][255][256], result-ing in improved Indigenous health knowledge [257], improved knowledge about Indigenous perspectives, commitment to rural and underserved areas [255], and improved cultural responsiveness within healthcare settings [254].…”
Section: Reducing Trauma and Discriminationmentioning
confidence: 99%
“…This situation is gradually changing, as some medical and nursing schools have become increasingly informed about safe, culturally congruent, and evidence-based alternative, complementary, and integrative approaches to health care delivery. 3,4,5,6,7,8,9,10 Patient challenges. TM/H is critical to the identity and culture of tribal nations and the ways that they relate to the world around them.…”
Section: Practice Challengesmentioning
confidence: 99%